Presencia de Maimónides en una obra de Benjamin Galemiri: Jethro o la Guía de los perplejos - Thomas Dublé, Eduardo (Cuadernos Judaicos, 2008)
The dramatic work ofBenjamín Galemíri is characteristic for íts references to the most different texts and discourses of the western tradition. The Bible intertextos and other works related to the Jewish tradition are outstanding for its meaningful richness. In this work the intertextuality of his play Jethro or the Guide lor the Perplexed with Maimonides's: Perplexed Guide is studied, stressing the parodistic way of its text elaboration.